The Complexity of Occupational Stress Risk Factors among Seafarers - Santoso, Jemmi Wahyu; Widanarko, Baiduri (Jurnal Penelitian Kesehatan SUARA FORIKES, 2026)
Occupational stress refers to harmful physical and emotional responses that arise when job demands exceed a worker’s capacity, resources, or needs. Prolonged exposure to such demands may adversely affect both mental and physical health. Previous studies indicate that seafarers are up to twice as vulnerable to stress-related risk factors compared with other occupational groups, potentially increasing the risk of illness and workplace accidents. This systematic literature review aimed to comprehensively identify risk factors associated with occupational stress among seafarers. Literature was retrieved from Scopus, PubMed, and Google Scholar using the keywords “work stress,” “risk factors,” “health and stress,” “psychosocial,” “job stress,” “stressors,” “seamen,” and “seafarers,” combined using the Boolean operators “OR” and “AND.” A total of 261 articles were identified and screened using the PRISMA flow diagram. Selected studies were critically appraised using the Joanna Briggs Institute (JBI) quality assessment tools. Of the 21 full-text articles assessed, eight met the inclusion criteria for systematic review. The findings identified 14 occupational stress risk factors among seafarers: age, gender, education level, marital status, smoking status, years of service, employment status, excessive workload, low workload, job-related boredom, job demands, time pressure, interpersonal relationships, and job security. In conclusion, occupational stress risk factors among seafarers are multifaceted and diverse, encompassing individual, occupational, and psychosocial dimensions. Comprehensive and multi-stakeholder interventions are therefore essential to effectively prevent and manage work-related stress in this population.Keywords: occupational stress; risk factors; seafarers